2009
DOI: 10.1021/es803112a
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Redox Changes by Microbially and Chemically Formed Semiquinone Radicals and Hydroquinones in a Humic Substance Model Quinone

Abstract: Arsenic is a redox-active metalloid whose toxicity and mobility strongly depends on its oxidation state, with arsenite (As(III)) being more toxic and mobile than arsenate (As(V)). Humic substances (HS) are also redox-active and can potentially react with arsenic and change its redox state. In this study we show that semiquinone radicals produced during microbial or chemical reduction of a HS model quinone (AQDS, 9,10-anthraquinone-2,6-disulfonic acid) are strong oxidants. They oxidize arsenite to arsenate, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 41 publications
5
68
1
Order By: Relevance
“…In contrast to microbial reduction experiments with FA and HA at neutral pH where high radical concentrations were found (Jiang et al 2009), in our setups where solutions of 10 mg/ml FA were incubated with strain SJH at acidic pH, no radical formation could be detected by ESR measurements (data not shown). Moreover, incubation of FA with H 2 /Pd at pH 2.3 also did not lead to increasing concentrations of radicals, although increasing Fig.…”
Section: Absence Of Radical Formation During Incubation Of Humic Subscontrasting
confidence: 69%
“…In contrast to microbial reduction experiments with FA and HA at neutral pH where high radical concentrations were found (Jiang et al 2009), in our setups where solutions of 10 mg/ml FA were incubated with strain SJH at acidic pH, no radical formation could be detected by ESR measurements (data not shown). Moreover, incubation of FA with H 2 /Pd at pH 2.3 also did not lead to increasing concentrations of radicals, although increasing Fig.…”
Section: Absence Of Radical Formation During Incubation Of Humic Subscontrasting
confidence: 69%
“…But as the swelling or shrinking of DOM molecules caused by pH or ionic strength variation shall also result in accessibility changes of the redox-active functionalities, the ETC of DOM are expected to change with the conformational alteration (swelling and shrinking) of DOM molecules induced by changes in the pH and ionic strength. During their research on the redox reaction between arsenic and semiquinone radicals, Jiang et al (2009) observed that the oxidizing capacity of semiquinone radicals is strongly pH dependent: more arsenite (up to 67.3 %) was oxidized at pH 11 than at pH 7 (12.6 % oxidation) and pH 3 (0.5 % oxidation). Quinone moieties are the main electron acceptors in DOM (Scott et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Organic free radicals are studied by electron paramagnetic resonance (EPR) spectroscopy (Tollin and Steelink 1966;Jiang et al 2009;Lodygin et al 2007;Spagnuolo et al 2005;Bialk et al 2005). The EPR-parameters of free organic radicals of humic acids (HA) and fulvic acids (FA) were estimated for a variety of samples taken from different surface waters and soils (Paul et al 2006;Jiang et al 2009). These authors showed that spin concentrations of the free organic radicals ranged from 0:64  10 17 spin  g À1 to 3:93  10 17 spin  g À1 for HA, and 0:54  10 17 spin  g À1 to 5:41  10 17 spin  g À1 for FA.…”
Section: Experimental Data Of Paramagnetic Properties Of Hsmentioning
confidence: 99%
“…Applications of HS already exist in medicine (especially in pharmacology), water purification techniques, and agriculture (Jiang et al 2009;Paul et al 2006). Examination of the influence of HS on reversible red cell aggregation, using addition of HS to blood in vitro (Inisheva et al 2008), showed their substantial effect on aggregation of red cells in blood in dependency on the method of HS extraction from peat and sapropel and the HS concentration applied to blood.…”
Section: Introductionmentioning
confidence: 99%